Adolescent Reproductive Health: The Role Of Sex Education In Raising Awareness - Wiwin Rohmawati; Mega Octamelia; Masnila Masnila; Nurlama Siregar (Oshada, 2024)
The first stage of labor often takes a long time and causes discomfort for the mother, so methods are needed to accelerate it. This study aims to evaluate the effectiveness of microcontroller-based nipple stimulation in accelerating the labor process by stimulating the release of the hormone oxytocin which increases uterine contractions and accelerates cervical opening. Microcontroller technology is used to ensure the stimulation is done automatically and measured according to the mother's physiological needs. This study involved two groups, namely the group that received stimulation and the control group that did not receive stimulation. The results showed that the stimulated group experienced shorter labor times than the control group and were less likely to require medical interventions such as induction with drugs.  Close monitoring is still required to ensure safety, especially regarding the risk of uterine hyperstimulation that may affect the condition of the mother and fetus. Further research is needed to test the long-term effectiveness and safety of this method before it is widely applied in obstetric practice. Based on the total library, 600 were identified and as many as 100 additional articles were identified. A total of 630 studies failed to meet the inclusion criteria and 70 articles were read in their entirety, so that as many as 11 publications were used as references. Microcontroller-based nipple stimulation offers an innovative solution that can improve the efficiency of labor while providing a better quality of health care.